Preparation and Evaluation of Microencapsulated Dexamethasone Sodium Phosphate Using Double Emulsion Method - Mohammed Wajeah Abdul Ameer; Nidhal K. Maraie (College of Pharmacy / Mustansiriyah University, 2019)
The need for producing sustained release dosage form was increased (especially for chronic diseases) to decrease side effect, increase efficacy of treatment, so it is now possible to administer the drugs once a week to once a year.     Dexamethasone sodium Phosphate (DSP) is a potent corticosteroid used for the treatment of many conditions like osteoarthritis (OA) and post joint replacement surgery. Microencapsulated dexamethasone sodium phosphate (DSP) having continuous prolonged release was prepared. To achieve that, DSP microcapsules were prepared using w/o/w double emulsion method where PLGA was used as a polymer, PVA and glycerol as plasticizer and Cetyl trimethyl ammonium bromide (CTAB) as emulsifying agent. Nine formulas of (PLGA coated (DSP) (microcapsules) were prepared to study the effect of different variables on the % yield and entrapment efficiency (EE) including the effect of internal aqueous phase volume, presence of NaCl (as osmotic pressure enhancer), PLGA concentration, plasticizer concentration and sonication time. The best formula was found to be formula (F1) containing 16 mg DSP coated with PLGA and found to give 85% EE and 94.19% yield.